2010
DOI: 10.1111/j.1471-0528.2010.02622.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute maternal social dysfunction, health perception and psychological distress after ultrasonographic detection of a fetal structural anomaly

Abstract: Please cite this paper as: Kaasen A, Helbig A, Malt U, Næs T, Skari H, Haugen G. Acute maternal social dysfunction, health perception and psychological distress after ultrasonographic detection of a fetal structural anomaly. BJOG 2010;117:1127–1138. Objectives  To predict acute psychological distress in pregnant women following detection of a fetal structural anomaly by ultrasonography, and to relate these findings to a comparison group. Design  A prospective, observational study. Setting  Tertiary referral ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 38 publications
6
84
0
4
Order By: Relevance
“…Additionally, it has been shown that prenatal diagnostic procedure can have a negative emotional impact on pregnant women [27][28][29]. The detection of a fetal anomaly generally determined an increase in psychosocial distress in both parents, and especially in women [30]. This is in line with our results: women carrying a fetus with an anomaly experienced higher anxiety and depression compared with women with a normal child.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, it has been shown that prenatal diagnostic procedure can have a negative emotional impact on pregnant women [27][28][29]. The detection of a fetal anomaly generally determined an increase in psychosocial distress in both parents, and especially in women [30]. This is in line with our results: women carrying a fetus with an anomaly experienced higher anxiety and depression compared with women with a normal child.…”
Section: Discussionsupporting
confidence: 94%
“…For example, a prospective study of women who had prenatal diagnosis of fetal structural anomaly by ultrasound reported that ambiguity regarding diagnosis [34], as well as uncertainty about prenatal outcome of the fetus to be associated with high psychological distress [35]. Another study showed that false positive soft markers in prenatal ultrasound screening provoked maternal anxiety during pregnancy [36] and reduced early mother-infant interaction at 2 months after giving birth, although the infant was normal.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of anxiety and psychological distress have been documented in pregnant women for whom a foetal malformation is suspected [5][6][7][8], diagnosed [8,9], or when prenatal diagnosis appears ambiguous [9]. The finding of a SM is also associated with psychological distress and anxiety [10].…”
Section: Introductionmentioning
confidence: 99%